Horner syndrome due to blunt thoracic trauma. (June 2019) - Moraga, Eduardo Leyva; Celaya, Jesús Martín Ibarra; Rodriguez, Marco Antonio McGahey; Moraga, Francisco Leyva; Ortega, Graciano Castillo; Moraga, Fernando Leyva
A relationship between Horner syndrome and thoracic trauma is exceedingly rare. We present the case of a 46-year-old man who was brought to our center after an accidental fall from a height of 4 meters. He sustained multiple ribs fractures as well as scapular and clavicle fractures in the left hemithorax. During his hospital stay, he developed Horner syndrome due to a posterior fracture of the first rib.